The Immune Checkpoint BTLA in Oral Cancer: Expression Analysis and Its Correlation to Other Immune Modulators - Ries, Jutta; Trumet, Leah; Hahn, Alina; Kunater, Lina; Lutz, Rainer; Geppert, Carol-Immanuel; Kesting, Marco Rainer; Weber, Manuel (International Journal of Molecular Sciences, 2024)
In oral squamous cell carcinoma (OSCC) tissues, an immunotolerant situation triggered by immune checkpoints (ICPs) can be observed. Immune checkpoint inhibitors (ICIs) against the PD1/PD-L axis are used with impressive success. However, the response rate is low and the development of acquired resistance to ICI treatment can be observed. Therefore, new treatment strategies especially involving immunological combination therapies need to be developed. The novel negative immune checkpoint BTLA has been suggested as a potential biomarker and target for antibody-based immunotherapy. Moreover, improved response rates could be displayed for tumor patients when antibodies directed against BTLA were used in combination with anti-PD1/PD-L1 therapies. The aim of the study was to check whether the immune checkpoint BTLA is overexpressed in OSCC tissues compared to healthy oral mucosa (NOM) and could be a potential diagnostic biomarker and immunological target in OSCC. In addition, correlation analyses with the expression of other checkpoints should clarify more precisely whether combination therapies are potentially useful for the treatment of OSCC. A total of 207 tissue samples divided into 2 groups were included in the study. The test group comprised 102 tissue samples of OSCC. Oral mucosal tissue from 105 healthy volunteers (NOM) served as the control group. The expression of two isoforms of BTLA (BTLA-1/2), as well as PD1, PD-L1/2 and CD96 was analyzed by RT-qPCR. Additionally, BTLA and CD96 proteins were detected by IHC. Expression levels were compared between the two groups, the relative differences were calculated, and statistical relevance was determined. Furthermore, the expression rates of the immune checkpoints were correlated to each other. BTLA expression was significantly increased in OSCC compared to NOM (pBTLA_1 = 0.003; pBTLA_2 = 0.0001, pIHC = 0.003). The expression of PD1, its ligands PD-L1 and PD-L2, as well as CD96, were also significantly increased in OSCC (p ≤ 0.001). There was a strong positive correlation between BTLA expression and that of the other checkpoints (p < 0.001; ρ ≥ 0.5). BTLA is overexpressed in OSCC and appears to be a relevant local immune checkpoint in OSCC. Thus, antibodies directed against BTLA could be potential candidates for immunotherapies, especially in combination with ICI against the PD1/PD-L axis and CD96.
CRIS-Team Scopus Importer:2024-07-12
Keywords: BTLA; CD96; immune checkpoints; immune therapy; oral squamous cell carcinoma; OSCC; PD-L1; PD-L2; PD1

The Immune Checkpoint Receptor CD96: A Local and Systemic Immune Modulator in Oral Cancer? - Trumet, Leah; Weber, Manuel; Hahn, Alina; Kunater, Lina; Geppert, Carol-Immanuel; Glajzer, Jacek; Struckmeier, Ann-Kristin; Möst, Tobias; Lutz, Rainer; Kesting, Marco Rainer; Ries, Jutta (Cancers, 2023)
Background: As immunotherapy of oral squamous cell carcinomas (OSCCs), using PD1 inhibitors, is only efficient in a small proportion of patients, additional immune checkpoints need to be identified as potential therapeutic targets. There is evidence that a blockade of CD96 might positively affect the anti-tumor immune response. The aim of this study was to analyze the gene and protein expression of CD96 in the tissue and peripheral blood of OSCC patients compared to healthy controls, while also checking for potential associations with a differential expression to the histomorphological parameters. In addition, possible correlations with the expression of PD1 and PD-L1 as well as the macrophage markers CD68 and CD163 should be tested to obtain further insights into the potential effectiveness of combined checkpoint blockage. Material and Methods: For real-time quantitative polymerase chain reaction (RT-qPCR), a total of 183 blood and tissue samples, divided into a patient and a control group, were included. Additionally, 141 tissue samples were examined by immunohistochemistry (IHC). The relative expression differences between the groups were calculated using statistical tests including the Mann–Whitney U test and AUC method. The Chi-square test was used to determine whether CD96 overexpression in individual samples is associated with malignancy. Correlation analysis was performed using the Spearman correlation test. Results: There was a significant CD96 mRNA and protein overexpression in the OSCC group compared to the controls (p = 0.001). In contrast, CD96 mRNA expression in the peripheral blood of the OSCC patients was significantly lower compared to the control group (p = 0.007). In the Chi-square test, the OSCC tissue samples showed a highly significant upregulation of CD96 mRNA expression (p < 0.001) and protein expression (p = 0.005) compared to the healthy mucosa. CD96 mRNA and protein expression correlated significantly (p = 0.005). In addition, there was a significant positive correlation of CD96 expression with PD1 (p ≤ 0.001), PD-L1 (p ≤ 0.001), and CD163 (p = 0.006) at the mRNA level. Conclusions: CD96 expression in the tumor tissue and peripheral blood of OSCC patients is differentially regulated and appears to be a relevant immune checkpoint.
CRIS-Team Scopus Importer:2023-04-28
Keywords: HNSCC; immune checkpoints; immunotherapy; OSCC; PD-1; PD-L1